The use of wait-time in questioning during reading comprehension lesson by secondary school teachers in Selangor - Harvindar, Kaur; Hashim, Che Noraini (Research Institute for Progression of Knowledge (RIPK), U.K, 2014)
Questioning is pivotal in reading comprehension lessons in particular and classrooms in general. One of widely used questioning strategies is wait-time. Thus this study is aimed at investigating the use of wait-time during reading comprehension lessons by two English teachers at a school in Selangor. They were selected using the purposive sampling method. The data were collected through individual-in-depth interviews. The interviews were transcribed verbatim and thereafter analysed using the process of coding and generating themes. Findings revealed that ‘duration’, ‘question type’ and ‘proficiency level’ were the themes generated with regard to the amount of wait time teachers allowed their students to have while ‘facts’, ‘cognition’, ‘communication’, ‘teacher’s perception’ and ‘response type’ were the themes that emerged for the reasons teachers used waittime during questioning. This study some implications for teachers. Teachers should learn questioning skills and specifically about the wait-time strategy as both teachers in this study were not aware of the term wait-time. In order to aid this process, the ministry of education should conduct training sessions to expose teachers to classroom questioning and the use of wait time in class. However, in this case study only two respondents were interviewed and both were females. Perhaps future researchers should select a large sample involving numerous schools in the future so the findings can be generalised to other teachers in Malaysia.